LD50 ACUTE TOXICITY TEST OF GREEN GRASS JELLY (Cyclea barbata Miers) LEAF EXTRACT AGAINST MICE (Mus musculus L.): UJI TOKSISITAS AKUT LD50 EKSTRAK DAUN CINCAU HIJAU (Cyclea barbata Miers) TERHADAP MENCIT (Mus musculus L.) - Hendri Poernomo; Taha Ma'aruf; Ari Sucitra Dewi (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Green grass jelly leaves (Cyclea barbata Miers) are well known by the public as food to reduce fever (fever), nausea, stomach ulcers, coughs and reduce high blood pressure, antioxidants, anti-inflammatories, and as analgesics, so safety needs to be controlled. Acute Toxicity Test is a test used to detect the toxic effect of a substance on a biological system and to obtain typical response data from test preparations, Lethal Dose 50 and toxicity classification. Research Objectives: To determine the safety of green grass jelly leaf extract (Cyclea barbata Miers) against mice (Mus musculus L.) by LD50 acute toxicity test. Research Methods: In the acute toxicity test using the Thomson-Weil calculation method and mice as experimental animals as many as 25 mice (Mus musculus). The mice were divided into 5 treatment groups with the main test series group I distilled water as the control, group II was given the test extract at a dose of 200 mg/kg, group III was given the test extract at a dose of 400 mg/kg, group IV was given the test extract at a dose of 800 mg/kg, and Group V was given the test extract at a dose of 1600 mg/kgBW with one oral administration and observed the number of deaths in each test animal after 24 hours to 14 days. Research Results: The results of the acute toxicity test showed that the LD50 value of green grass jelly leaf extract was 0.6166 gr/kg BW (moderately toxic). For acute toxicity, the weights of mice were analyzed using the ANOVA and LSD tests and for allergy testing using the Wilcoxon signed ranks test. Conclusion: the results of the analysis show that there is a significant difference at the test level of 0.05 (???? < 0.05).